Selective metal sensor phthalocyanines bearing non-peripheral functionalities: Synthesis, spectroscopy, electrochemistry and spectroelectrochemistry - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
A novel alcohol-soluble ionophore ligand and its non-peripherally tetrasubstituted functional 1,8,15,22-tetrakis(6-hydroxyhexylsulfanyl) metallophthalocyanines M[Pc(alpha-SC(6)H(12)OH)(4)] (M = Cu(II), Zn(II), Co(II); Pc=phthalocyanine) are reported. The aggregation and cation binding behaviors of the phthalocyanine compounds in the presence of soft Ag(I) and Pd(II) metal ions were investigated by using UV-Vis spectroscopy. The new compounds have been characterized by elemental analysis, IR, (1)H, (13)C NMR, UV/Vis spectroscopy, ESI and MALDI-TOF-MS mass spectra. Voltammetric and in-situ spectroelectrochemical studies show that while copper and zinc phthalocyanine complexes give well-defined ring-based reduction and oxidation processes, the cobalt phthalocyanine gives both metal-based and ring-based redox processes which have reversible and diffusion controlled character. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanines; Metal sensor; Aggregation; Electrochemistry; Spectroelectrochemistry; ION BINDING; WATER; METALLOPHTHALOCYANINES; PORPHYRAZINES; SUBSTITUENTS; THIOPHENES; COBALT; COPPER; OXYGEN